2003
DOI: 10.1016/s0928-8244(03)00241-4
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the first complete hepatitis E virus (HEV) genome from Africa

Abstract: Hepatitis E virus (HEV) is globally distributed, transmitted enterically and between humans and animals. Phylogenetic analysis has identified five distinct HEV genotypes. The first full-length sequence of an African strain (Chad) is presented and compared to 31 complete HEV genomes available, including the fulminant hepatitis strain from India, swine strains and a strain from Morocco. The two African strains are more closely related to genotype 1 than to any other genotypes and together they possibly form a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Table  5 presents a summary sorted by genotype and also provides characteristics of the sample, genomic regions tested. Genotype 1 seems to be most prevalent as it was found in Central African Republic [34], Sudan [35], Chad [28,35], Egypt [46,62,124], and Namibia [88] followed by genotype 2, which were observed in Central African Republic [34], Chad [35], Namibia [87], and Nigeria [6,89]. Genotype 3 is rare and was found in one Egyptian child [48], one acute hepatitis patient in Mayotte (originally from France) [82].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table  5 presents a summary sorted by genotype and also provides characteristics of the sample, genomic regions tested. Genotype 1 seems to be most prevalent as it was found in Central African Republic [34], Sudan [35], Chad [28,35], Egypt [46,62,124], and Namibia [88] followed by genotype 2, which were observed in Central African Republic [34], Chad [35], Namibia [87], and Nigeria [6,89]. Genotype 3 is rare and was found in one Egyptian child [48], one acute hepatitis patient in Mayotte (originally from France) [82].…”
Section: Resultsmentioning
confidence: 99%
“…We also discuss studies of sporadic cases and outbreaks of NANB hepatitis viruses in the Discussion Section with tables of data in the Additional file 1. The present paper includes studies from 28 (50%) of 56 African countries: Algeria [26-28], Burkina Faso [29], Burundi [30,31], Cameroon [32], Central African Republic [33,34], Chad [27,28,35-38], Côte d’Ivoire [39], Democratic Republic of the Congo [40], Djibouti [41,42], Ethiopia [6,43], Eritrea [44], Egypt [45-71], Gabon [72,73], Ghana [32,74-78], Kenya [79,80], Madagascar [81], Mayotte [82], Morocco [83-85], Namibia [86-88], Nigeria [89-91], Senegal [92,93], Somalia [94-96], South Africa [97,98], South Sudan [99], Sudan [35,100-105], Tunisia [106-111], the United Republic of Tanzania [112-114], and Zambia [115]. …”
Section: Methodsmentioning
confidence: 99%
“…The comparison of these sequences with other HEV sequences from the same region showed that these isolates are related to Genotype 1, sharing 88% homology with the prototype Burmese strain (Genbank Accession Number M72318) and 93% identity with a Chad strain (Genbank Accession Number AY204877) collected in 1983 from a patient with hepatitis E (Fig. 1) [van Cuyck et al, 2003]. The remaining four isolates from Goz Amer camp shared 100% similarity.…”
Section: Resultsmentioning
confidence: 96%
“…Genotype 1 extensively circulates in Asia (including India, 7578 Pakistan, 79 Nepal, 80, 81 Bangladesh, 82 China, 49, 8385 Kyrgyzstan, 86 and Uzbekistan 87 and Africa (including Egypt, 88 Algeria, 89 Morocco, 87 Namibia, 90 Sudan, 91 and Chad 91, 92 ), whereas genotype 2 has been isolated only in Mexico 93 and in some African countries (Nigeria, 94 Namibia, 95 Chad, 91 and Sudan 91 . Genotype 3 has been detected worldwide (America, 13, 26, 32, 33, 96–99 Europe, 9, 10, 12, 15, 16, 18, 20, 21, 27, 34, 35, 100102 Asia, 25, 33, 37, 39, 40, 103111 Australia, 69 and New Zealand 11 with the exception of Africa, whereas genotype 4 is restricted to India 112, 113 and East Asia.…”
Section: Epidemiologymentioning
confidence: 99%